(untitled) (Zaporizhzhia Historical Review, 2021)
According to the data of the register of deaths from the village of Lukyanivka the mortality indicators of the peasant population in Pereyaslavschina in the second half of the 18th c. are analyzed in the article. The seasonal changes of the mortality indicators are researched. The influence of the indicators on the natural movement of population is ascertained